STUDI KESESUAIAN PERENCANAAN TANAMAN KARET DI WILAYAH KPHP DAMPELAS-TINOMBO DESA KARYA MUKTI KECAMATAN DAMPELAS KABUPATEN DONGGALA - Kurniawan, Agung Dwi; Akhbar, Akhbar (Universitas Tadulako, 2020)
The research of the suitability of rubber plant planning studies at the kphp area of dampelas tinombo. The research was conducted to determine the suitability of the management plan from the preparation stage to the stage of harvesting rubber plantations which involved the community in its implementation. This research conducted in the village of Karya Mukti, Dampelas Subdistrict - Donggala District, in 3 months. The data analysis technique used in this study are descriptive and comparative analysis, where the source of the data came from interviews and technical designs of forest and land rehabilitation activities. The results of this study indicated that planting activities, facilities and infrastructure, seed requirements and seed supply alternatives, material and equipment needs, group institutions, technical guidance, and training are in accordance with existing technical designs, while nursery, maintenance, protection and supervision activities , counseling and assistance, and product marketing.Keywords: KPHP Dampelas - Tinombo, Rubber Plant Planning, Forestry Planning